Aged Turkey manure shapes microbial diversity and antibiotic resistance genes in soil and plants under fertilization - Attanayake Mudiyanselage Ransirini; Mierzejewska-Sinner Elżbieta; Giebułtowicz Joanna; Kózka Bartosz; Kupiec Jerzy Mirosław; Urbaniak Magdalena (Scientific Reports)
Abstract The growing use of animal manure in agriculture has raised concerns about its impact on soil health and the dissemination of antibiotic resistance genes (ARGs), particularly from less-studied sources like Turkey manure. Despite its widespread use, little is known about how aged Turkey manure affects soil–plant systems. This study investigates its influence on soil physicochemical properties, microbial diversity, and the distribution of ARGs. Soil properties changed significantly following Turkey manure fertilization, with organic carbon, humus contents and C/N ratio decreasing by 19%, 20%, and 9%, respectively, indicating enhanced nitrogen mineralization and increased microbial activity. Turkey manure-amended variants exhibited greater microbial diversity, particularly among leaf endophytes, as indicated by an increase in AWCD from 0.02 to 0.32. In contrast, root endophytes showed higher microbial diversity in the control group (AWCD 0.97 vs. 0.91). Diversity indices, including the Shannon–Weaver index (H') and evenness (E), were higher in the manure-treated samples compared to the controls, although the differences were not statistically significant. However, substrate richness (S) increased significantly in the leaf endophyte samples, rising from S=1 in the control to S=12 in the manure-treated samples. ARGs were detected exclusively in manure-amended samples. The β-lactam resistance gene blaTEM was detected in aged manure, soil, and leaf endophytes. Tetracycline resistance genes (tetA, tetc, and tetM) persisted in the soil over time, whereas the resistance genes of the MLS (linA) and fluoroquinolone (aac(6')-Ib-cr) strains were transient and appeared only early in the experiment. ARGs, including β-lactam, tetracycline, and fluoroquinolone resistance genes, are absent in root endophytes but are present in leaf endophytes, raising food safety concerns. In conclusion, aged Turkey manure altered soil physicochemical properties, enhanced microbial diversity, and influenced the distribution of ARGs in the soil–plant system, highlighting the need for a more balanced manure management to improve soil health while limiting ARG dissemination.